The Internet as a global good: UNESCO's attempt to negotiate an international framework for universal access to cyberspace - Julia Pohle (International Communication Gazette, 2018)
The article analyzes one of the earliest intergovernmental initiatives regarding Internet constitutionalism. Based on an analytical framework that combines argumentative discourse analysis with elements from actor–network theory, it assesses the actors and discourses involved in the preparation of an international recommendation on universal access to the Internet, adopted by the United Nations Educational, Scientific, and Cultural Organization (UNESCO) in 2003. During the contentious negotiations, UNESCO had to find a balance between the divergent positions of its member states and to account for the different levels of technological development amongst them. By retracing the performative and discursive struggles that UNESCO had to face to reach consensus, the article contributes to the general understanding of ideas and practices behind Internet policy making in international settings.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; communication studies; intergovernmental organization; Internet constitutionalism; Internet regulation; policy discourse; public domain; UNESCO; universal access